In Search of the Perennial Orgasm, a Perception From Total Quality, Globalization in Education and Didactic Approaches (Global Journal of Human-Social Science, 2024)
Continuous improvement in search of comprehensive excellence should embrace all possible systems and institutions in a world in constant change and rethinking Education from its pedagogical and didactic nuance must be in tune and at the forefront The objective of this documentary horizon investigation is to address from the contrast the concept of Total Quality Globalization in Education and Didactic Approaches Conclusion Thirst nonconformity and desire for fulfillment are synonymous with being human In the search for the perennial orgasm it has made great progress but it has also at times become unfocused to the point of putting its own existence and that of the ecosystem that surrounds it at risk Could it be that we are repeating the fallacy Could it be that we have forgotten the founding and fundamental question
Keywords: total quality; education; didactic approaches; onticity